The national agents of transnational memory and their limits: the case of the Museum of the Second World War in Gdańsk. Issue 2 (3rd April 2019) - Siddi, Marco; Gaweda, Barbara
ABSTRACT: This article examines the drivers and limiting factors of the transnationalisation of Second World War memory by focusing on the recently opened Museum of the Second World War in Gdańsk. The creators of the museum presented it as an attempt to internationalise the memory of the conflict through the inclusion of East-Central European perspectives. The article contends that large parts of the exhibition foregrounded Polish narratives of the conflict. The exhibition reflected the intent of placing Polish (and through them East-Central European) perspectives at the centre of a broader transnational framework, and thus influence both the domestic and the international debate on the memory of the war. The article argues that the national agency from which the museum originated constituted the main limitation to the declared goal of providing a transnational narration of the war. This became particularly evident when the nationalist and conservative Law and Justice party rose to power in Warsaw and modified the structure of the museum. As part of a wider chauvinist memory politics, the new authorities weakened the transnational references in the exhibition and strengthened nationalist, Poland-centric narratives. The article concludes by arguing that national-level agency alone appears inadequate to sustain the transnationalisation of Second World War memory.